2012
DOI: 10.1007/s00436-012-2966-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pediculus humanus capitis infestation among kindergarten children in Bahía Blanca city, Argentina

Abstract: The human head louse, Pediculus humanus capitis De Geer (Anoplura: Pediculidae), is a worldwide public health concern. This human obligate ectoparasite usually infests school age children. The aim of this work was to investigate the prevalence of head lice in kindergarten children from Bahia Blanca. In addition, the influence of risk factors for pediculosis infestation, such as gender, hair characteristics, and socioeconomic class, was studied in relation to the prevalence of this ectoparasite. From a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
2
13
0
1
Order By: Relevance
“…Impact of socioeconomic conditions of families on children's head lice infestation has been reported inconsistently (Chouela et al 1997;Gutiérrez et al 2012;Mahmud et al 2011). However, pediculosis has been linked to social classes with low economic and cultural resources.…”
Section: Discussionmentioning
confidence: 94%
“…Impact of socioeconomic conditions of families on children's head lice infestation has been reported inconsistently (Chouela et al 1997;Gutiérrez et al 2012;Mahmud et al 2011). However, pediculosis has been linked to social classes with low economic and cultural resources.…”
Section: Discussionmentioning
confidence: 94%
“…This study reported the overall prevalence of 13.1% in the city of Kayseri, Turkey. Epidemiological studies performed in primary schoolchildren found that the prevalence of pediculosis capitis was 28.8% in England, 1.59% in Poland, 8.9% in Belgium, 15% in France, 9.39% in Spain, 78.6% in Libya, 55% in Israel, 8% in Lebanon, 26.6% in Jordan, 6.85% in Iran, 16.59% in India, 40% in Taiwan, 4.1% in Korea, 33.7% in Australia, 42.7% in Brazil, and 29.7% in Argentina (1,4,5,7,(10)(11)(12)(13)(14)(15). The prevalence of head lice in Turkey varied geographically: 9.5% in Eastern Turkey, 2.2% in Western Turkey, 6.8% in Southern Turkey, and 5.4% in Northern Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we did not evaluate the influence of hair length on head lice prevalence. Skin factors or effects of hormones such as progesterone and prolactin may be associated with this tendency (1,7,10,11,15). Low prevalence in boys could be explained by the hypothesis that short hair of boys impedes detection of an infestation (5,9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations